2020
DOI: 10.3389/feduc.2020.00027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Science Capital on Self-Concept in Science: A Study of University Students in New Zealand

Abstract: Understanding factors that contribute to students' self-concept in science is an important task in boosting the number of students studying science and retaining students in science fields. A questionnaire was administered to science students at the University of Auckland in New Zealand (N = 693) to test a theoretical model of science self-concept tied to the work of Pierre Bourdieu. In this model, a student's social capital (i.e., relationships with parents, teachers and peers) and cultural capital (i.e., sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
2
11
0
1
Order By: Relevance
“…In our data students' participation in cultural activities does not significantly affect achievement in mathematics and this suggests "cultural capital does affect educational outcomes, but in a limited way" (Dumais, 2002, p. 59). This finding is also consistent with a recent study in the related domain of science, which found that familial science capital had a small impact on science self-concept when compared to the larger effect of social class indicators (Turnbull et al, 2020). However, when habitus, which is operationalised as students' mathematicsrelated career aspirations, is added to the model after cultural capital, it showed a 2.3% increase of variance in GCSE achievement.…”
Section: Discussionsupporting
confidence: 90%
“…In our data students' participation in cultural activities does not significantly affect achievement in mathematics and this suggests "cultural capital does affect educational outcomes, but in a limited way" (Dumais, 2002, p. 59). This finding is also consistent with a recent study in the related domain of science, which found that familial science capital had a small impact on science self-concept when compared to the larger effect of social class indicators (Turnbull et al, 2020). However, when habitus, which is operationalised as students' mathematicsrelated career aspirations, is added to the model after cultural capital, it showed a 2.3% increase of variance in GCSE achievement.…”
Section: Discussionsupporting
confidence: 90%
“…Bourdieu's theory of social and cultural reproduction has created a new coherent view of the sociology of education. His sociological framework is based on the sociology of power [32] and it is particularly useful for investigating how resources are allocated in society and how a person's internal dispositions are influenced by society's external structures [56]. His work on social reproduction has been widely employed in education research to investigate and understand the tenacity of stratified social patterns.…”
Section: Theoretical Framework: Bourdieu's Sociology Of Educationmentioning
confidence: 99%
“…• objectified capital which refers to cultural goods like books, instruments, machines and it necessitates embodied capital to be fully valued [12]. • institutionalised capital which is a form of objectification e.g., formal qualifications Social capital refers to relationships between individuals that facilitate the growth of the other forms of capital [56]. Social capital inclines an investment in social relationships that would generate beneficial outcomes [46].…”
Section: Capitalmentioning
confidence: 99%
See 2 more Smart Citations